Effectiveness of the Kinetic Wedge foot orthosis modification to improve gait posture - Rambarran, Kerry K (University of Ottawa (Canada), 2003)
Clinically, Functional Hallux Limitus (FHL) has been identified as a contributor to the disruption of proper progression of the inverted pendulum through the sagittal plane. The Kinetic Wedge Custom Foot Orthotic (CFO) modification has been used by the podiatric community to facilitate proper first metatarsal-phalangeal (MTP) joint function and improve gait posture. The aim of this study was to determine the effectiveness of the Kinetic Wedge custom foot orthosis (CFO) modification to improve gait, posture, centre of pressure velocity, plantar pressures of the foot, and perceived pain. Fifteen healthy subjects (9 women, 6 men) 22 to 53 years of age diagnosed with moderate to severe FHL volunteered for the study. Kinematic and plantar pressure data were collected without Kinetic Wedge (NKW) and with Kinetic Wedge(KW). There was a significant reduction of plantar pressure under the first MTP, however, there were no significant changes in plantar pressures under the hallux and fifth metatarsal. There was no significant difference in centre of pressure velocities. In addition, there were no significant increases in trunk, hip, knee, and ankle range of motion. Furthermore, self perceived pain did not significantly reduce 2 months after testing.
Keywords: Health Sciences, Rehabilitation and Therapy.